Using Social Judgment Theory method to examine how experienced occupational therapy driver assessors use information to make fitness-to-drive recommendations. (February 2015) - Unsworth, Carolyn; Harries, Priscilla; Davies, Miranda
Introduction: As people with a range of disabilities strive to increase their community mobility, occupational therapy driver assessors are increasingly required to make complex recommendations regarding fitness-to-drive. However, very little is known about how therapists use information to make decisions. The aim of this study was to model how experienced occupational therapy driver assessors weight and combine information when making fitness-to-drive recommendations and establish their level of decision agreement. Method: Using Social Judgment Theory method, this study examined how 45 experienced occupational therapy driver assessors from the UK, Australia and New Zealand made fitness-to-drive recommendations for a series of 64 case scenarios. Participants completed the task on a dedicated website, and data were analysed using discriminant function analysis and an intraclass correlation coefficient. Results: Accounting for 87% of the variance, the cues central to the fitness-to-drive recommendations made by assessors are the client's physical skills, cognitive and perceptual skills, road law craft skills, vehicle handling skills and the number of driving instructor interventions. Agreement (consensus) between fitness-to-drive recommendations was very high: intraclass correlation coefficient = .97, 95% confidence interval .96–.98). Conclusion: Findings can be used by both experienced and novice driver assessors to reflect on and strengthen the fitness-to-drive recommendations made to clients.